THE GREAT RETENTION: CULTIVATING A CULTURE WHERE PEOPLE STAY - Fini Fisielia; Ramon Zamora; Lukmanul Hakim (RADJA PUBLIKA, 2025)
In many organizations, employee recognition remains a generic, infrequent practice, failing to impact morale or retention meaningfully. This creates a culture where employees feel undervalued, leading to disengagement and turnover. This paper examines the framework of